2018
DOI: 10.1161/atvbaha.118.311186
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Ischemia Promote a Maladaptive Platelet Phenotype

Abstract: Objective Reduced blood flow and/or tissue oxygen tension conditions result from thrombotic and vascular diseases such as myocardial infarction, stroke, and peripheral vascular disease. It is largely assumed that while platelet activation is increased by an acute vascular event, chronic vascular inflammation, and/or ischemia, the platelet activation pathways and responses are not themselves changed by the disease process. We therefore sought to determine whether the platelet phenotype is altered by hypoxic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 52 publications
2
35
0
1
Order By: Relevance
“…Determination of a gender-specific difference in these clinical situations as we present here is a logical extension of those previous studies. We previously reported that proteomic profiles, agonist sensitivity, and anti-platelet medication efficacy are altered in humans and in murine models of MI and peripheral artery disease (1,3). We now suggest, based on the present data, that platelets in patients with acute MI are primed toward augmented PAR signaling in men.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Determination of a gender-specific difference in these clinical situations as we present here is a logical extension of those previous studies. We previously reported that proteomic profiles, agonist sensitivity, and anti-platelet medication efficacy are altered in humans and in murine models of MI and peripheral artery disease (1,3). We now suggest, based on the present data, that platelets in patients with acute MI are primed toward augmented PAR signaling in men.…”
Section: Discussionsupporting
confidence: 61%
“…The mature platelet has a surprisingly dynamic protein expression profile which may be responsible for changes in platelet phenotype. Based on changes in agonist sensitivity, the response to anti-platelet agents, and platelet proteomic profiles, we concluded that the mature platelet phenotype can change in vivo and in vitro in humans and in mouse models of hypoxic and ischemic disease (21). Given our present observation that platelet thrombin signaling differs in men and women in health and following MI, we employed an established murine MI model previously found to have ongoing thrombin-mediated platelet activation in the post MI environment (2).…”
Section: Sex Differences In Platelet Signaling In Healthy Mice and Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a mesenteric FeCl 3 injury model, Erk5 −/− mice had significantly delayed thrombus formation, suggesting that ERK5 regulates platelet function in a ROS dependent manner 74 . This ROS dependent mechanism was further codified when it was observed that ERK5 is activated in human platelets isolated from patients with peripheral artery disease or with ST‐elevation myocardial infarction 47,90 …”
Section: Erk5 Mapk Signaling and Platelet Functionmentioning
confidence: 99%
“…Platelets are the principal reservoir of CD154 in blood, being readily present and activated in inflamed tissues an important mechanism that provides CD154 in the inflammatory milieu [50]. In vivo, higher platelet reactivity and response to agonists observed in low O 2 conditions suggest that hypoxia favors platelet activation [51,52]. Whether in vivo hypoxia per se is an inducer of platelet activation remains debated.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%